Longitudinal changes on liver proton density fat fraction differ between liver segments - Syvaeri, Jan; Junker, Daniela; Patzelt, Lisa; Kappo, Katharina; Al Sadat, Loubna; Erfanian, Sonia; Makowski, Marcus R.; Hauner, Hans; Karampinos, Dimitrios C. (Quantitative Imaging in Medicine and Surgery, 2021)
Background: To study the spatial heterogeneity of liver fat fraction changes during a long-term lifestyle intervention study using magnetic resonance imaging (MRI). Methods: Thirty-two subjects underwent two MRI-scans in a span of one year. A chemical shift encoding-based water-fat separation method was applied to measure liver proton density fat fraction (PDFF) maps. The PDFF changes in the two liver lobes and the Couinaud segments were compared with the mean liver PDFF change. Results: The slope of the relationship between mean liver PDFF changes and PDFF liver lobe changes was higher in the right compared to the left lobe (slopemean PDFF whole liver mean PDFF right lobe =1.08, slopemean PDFF whole liver mean PDFF left lobe =0.93, P<0.001). The highest slope of agreement between PDFF changes in each specific liver segment and mean liver PDFF changes was observed in segment VII (slope =1.12). The lowest slope of agreement between PDFF changes in each specific liver segment and mean liver PDFF changes was observed in segment I (slope =0.77). Conclusions: Larger PDFF changes in the right liver lobe were observed compared to PDFF changes in the left liver lobe (LLL) in subjects with both increasing and decreasing mean liver PDFF after one year. The results are in line with the existing literature reporting a heterogeneous spatial distribution of liver fat and highlight the need to spatially resolve liver fat fraction changes in longitudinal studies.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Dixon mri; Lifestyle intervention study; Liver fat fraction spatial heterogeneity; Proton density fat fraction (pdff); Quantitative mri